RNA interference silencing of interleukin-6 in mesenchymal stromal cells and antitumour efficacy against multiple myeloma cells - Teoh, Hoon Koon (2015)
Studies demonstrated that mesenchymal stromal cells (MSC) from bone marrow (BM) stroma produced high concentrations of interleukin-6 (IL-6) that promoted multiple myeloma growth. In view of the failure of IL-6 monoclonal antibody therapy to demonstrate substantial clinical responses in early clinical trials, more effective methods are needed to disrupt the favourable microenvironment provided by the BM. In this study, RNA interference (RNAi)-mediated silencing of IL-6 in MSC and the efficacy of these modified MSC on U266 multiple myeloma cell growth inhibition in vitro and in vivo were evaluated. IL-6 silencing in MSC was induced using two different pathways: (1) direct administration of synthetic IL-6 siRNA using lipofectamine 2000 transfection and (2) vector-based adenovirus vector encoding IL-6 shRNA. Firstly, IL-6 protein in MSC was significantly suppressed to 36.7% and 39.4% post IL-6 siRNA transfection and IL-6 shRNA transduction respectively by 120 h compared to control MSC (100%) (P<0.05, T-test with n = 3 independent replicates). MSC remained viable and maintained their immunophenotypic profile and trilineage differentiation capacities similar to control MSC indicating no unanticipated phenotypic changes or cellular toxicity post IL-6 silencing. Secondly, in vitro and in vivo growth inhibition of U266 cells were shown in the presence of MSC transfected with IL-6 siRNA or transduced with IL-6 shRNA. In vitro results from three independent replicates showed that MSC transfected with IL-6 siRNA significantly inhibited U266 growth to 52.8% and 66.9% by day three through cell-substrate and cell-cell interactions respectively (P<0.05, ANOVA). MSC transduced with IL-6 shRNA also inhibited U266 growth significantly to 53.1% and 74.4% by day five through cell-substrate and cell-cell interactions respectively (P<0.05, ANOVA). Results from subsequent in vivo study showed significant reduction of U266 average tumour volume to 232.3 mm3 and 331.7 mm3 by day 21 in nude mice co-injected with MSC transfected with IL-6 siRNA and MSC transduced with IL-6 shRNA respectively compared to control MSC (1162.9 mm3) (P<0.05, ANOVA with n = 5 mice/group). Further histological analysis also showed increasing presence of lymphocytic infiltrates and significant decrease of mitotic index from 21 in tumours co-injected with control MSC to 15 in both U266 tumours co-injected with MSC transfected with IL-6 siRNA and MSC transduced with IL-6 shRNA indicating reduction of proliferating cells in the treated tumours (P<0.05, ANOVA with n = 3 slides/group). In conclusion, both RNAi pathways were equally effective in suppressing IL-6 expression in MSC and displayed in vitro and in vivo antitumor efficacy against U266 cells. These findings support the feasibility of using RNAi as an alternative approach for targeted suppression of IL-6 in MSC to inhibit multiple myeloma cell growth.